ANALISIS BIOEKONOMI IKAN TENGGIRI BATANG (Scomberomorus Lineatus) DI KABUPATEN KUTAI KARTANEGARA - Achmad Rozali; Nurul Ovia Oktawati; Zul Asman Randika (Jurnal Pembangunan Perikanan dan Agribisnis, 2016)
The purpose of research is to analyze level production, level effort, economic rents optimal and resources of mackerel (Scomberomorus sp.) In the waters of Kutai Kartanegara. Based on the model of control (MEY), sustainable (MSY), Open (OA) on actual conditions. Based on the findings of research known that the production rate actual condition is 1338.28 tons/year (MSY), 16.92 tons/year (OA) and 1338.28 (MEY). Further efforts utilization rate mackerel on actual condition is 22304.29 trips/year (MSY), 0.0003 trips/year (OA) and travel 22234.07/year (MEY). The latter subsequently in the Economic rent value is 36146.13 million/year (MSY), 460.14 million/ year (OA) and 36146.49 (MEY).